On the Impact of Texture and Grain Size on the Pseudoelastic Properties of Polycrystalline Fe–Ni–Co–Al–Ti Alloy - Sobrero, Cesar Enrique (2020)
The effects of thermomechanical treatments on crystallographic texture and grain size evolution and their impact on the pseudoelastic properties in Fe41–Ni28–Co17–Al11.5–Ti2.5 (at.%) were studied in the present paper. The results show that cold rolling leads to brass-type texture in this alloy, which is typical for low stacking fault energy materials. Thermal treatments up to 1300 °C were conducted and it is shown that the presence of β-phase helps to control grain growth. After the dissolution of the secondary phase induced by heat treatment at higher temperatures, a strong {230}〈001〉 recrystallization texture evolves in cold rolled samples already upon imposing medium reduction ratios. Finally, good pseudoelastic properties are found in conditions being characterized by adequate texture and grain sizes spanning over the entire thickness of the samples tested.